2014
DOI: 10.1179/2042645314y.0000000091
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some treatments on emission of volatile organic compounds (VOC) from chips used in pellets making processes

Abstract: Emission of volatile organic compounds (VOC) from wood during processing to pelletssignificance of wood extractives. Cellulose, hemicelluloses and lignin are the main components of the cell wall in wood. Moreover, wood contains different amounts of extractives, depending on the wood species. Extractives in softwoods play an important role during processing of wood to different wood products. This work studies the influence of storage on the change of extractives as well as on the emission of monoterpenes (prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Moreover, the amount of cold-water extractives of spruce wood increases, indicating some hydrothermal degradation of wood during the process of pellet making. Especially, the pressing process at high temperature and pressure appears to thermally degrade wood [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the amount of cold-water extractives of spruce wood increases, indicating some hydrothermal degradation of wood during the process of pellet making. Especially, the pressing process at high temperature and pressure appears to thermally degrade wood [36].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the produced RDF, due to the risk of self-heating and, in consequence, fire and even explosion [20], is not stored longer than a couple of days. Similarly, wood pellets storage is not recommended to be longer than several days [36]. By analogy, in this paper, we focused on the proposed four days of CRDF storage as being the ‘worst case’ scenario for a production facility and explored VOC emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting results related to the emission of volatile organic compounds have been obtained by Gabriel et al (2014). They established that even after extraction of pine chips with ethanol-cyclohexane, a well-known method for removal of extractives, the chips still emit VOCs, albeit very small amounts.…”
Section: Factors Influencing Voc Emission From Wood and Wood-based Pamentioning
confidence: 99%
“…However, the content of the solvent that remains in the treated samples is high. Some studies have also shown that extraction with ethanol-cyclohexane can significantly reduce the emission of terpenes and aldehydes in pine [18]. The reduction of VOCs by extraction has not been widely used due to the high content of solvent that remains in the treated wood.…”
Section: Introductionmentioning
confidence: 99%
“…Alkali treatment is a common chemical treatment, and studies have shown that alkaline solutions can promote the hydrolysis of fats and resins in wood [19]. It has been found that the sodium hydroxide solution can partially remove terpenes and aldehydes from pine extract [18]. Sodium bicarbonate has been used as a buffer to significantly reduce the VOC contents in styrene-acrylate emulsion [20] and acrylic elastic emulsion [21].…”
Section: Introductionmentioning
confidence: 99%